Chronic Discharging Sinus of Upper Lid Due to the Missed Wooden Foreign Body - Singh, Anupam; Vathulya, Madhubari; Mittal, S. K.; Agrawal, Ajai; Kumar, Barun; Puthalath, Athul S; Jamil, Mahsa (Nepalese Journal of Ophthalmology, 2018)
Background: Foreign bodies of the orbit can have a diverse range of clinical presentations, which may be perplexing to the most Ophthalmologists. Wooden foreign bodies can remain quiescent for a long time, before presenting with various complications. We report a case of Post-traumatic chronic non-healing discharging sinus in the left upper lid, which on exploration revealed the presence of the missed wooden foreign body. Case: A 48-year-old male, presented to Ophthalmic OPD with a complaint of discharge from the left upper eyelid for 18 months. The patient had a history of minor trauma to the left upper eyelid while collecting wood in the forest, 18 months back. The patient was misdiagnosed on previous examinations elsewhere. The diagnosis of retained wooden foreign body was made at our center and surgical exploration was done to remove the same. Observation: On clinical examination, there was a 2-3mm long sinus in the left upper eyelid with purulent discharge and granulation tissue. Surrounding skin showed hyperpigmentation and excoriation. CT scan orbit was inconclusive. MRI orbit revealed a peripherally enhancing extraconal/conal collection in the left orbit with a central hypo intense structure suggestive of a foreign body. Surgical exploration of the wound was done and a small wooden foreign body measuring 9mm was removed with excision of the sinus tract. Conclusion: A history of trauma followed by chronic discharging sinus should evoke suspicion of a retained foreign body. Prompt imaging, followed by surgical exploration should be done to prevent misdiagnosis and inappropriate management.